Big Data Review of East Java Community Compliance Index Against the Recommendation of Stay At Home During the Covid-19 Pandemic - Afrianto, Firman; Hariyanto, Annisa Dira (Faculty of Computer Science (FILKOM) Brawijaya University, 2022)
The Covid-19 pandemic period provides a change in the framework of discovering community mobility patterns as the basis for determining policies to control the spread of the virus. Big Data then becomes one of the indicators in finding mobility patterns because, while doing their activities, the internet and social media users continuously carry out even when staying at home. The Indonesian government controls the spread by issuing the Large-Scale Social Restrictions (PSBB) policy in 2020 and the Enforcement of Restrictions on Community Activities (PPKM) in 2021 and 2022. East Java Province is confirmed to have the highest level of COVID-19 spread in Indonesia, so it requires a pattern of proper handling to control its spread. This study provides information on the compliance index to the stay-at-home recommendations during the PSBB and PPKM periods. Wherefrom the Big Data analysis and Nighttime Light satellite imagery, the highest level of compliance occurred during PPKM in February 2022. Also, in general, the compliance index of the people of East Java is increased.